Fogging Effectiveness Based on Time and Location of DHF Cases (Study in Sleman Regency) (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Dengue fever is a viral infection transmitted through the bite of the Aedes mosquito. Dengue fever is a public health problem worldwide, including in Indonesia. The increase in dengue cases is closely related to the presence of mosquito vectors. The prevention of dengue outbreaks is by fogging focus. Until now, there is no method to evaluate the effectiveness of focal fogging, yet many suspect that fogging focus is less effective because the incidence of DHF tends to increase over several decades. The study aims to find a method to evaluate the effectiveness of fogging with a spatial-temporal approach. It is an observational study using data on the incidence of DHF along with the date of illness, coordinates of DHF patients, and the date of fogging obtained from the District Health Office. Data processing is by ArcMap 10.5. Determination of the time limit and extent of protective fogging is based on the provision that if in the buffer area within a radius of 200 meters, there is more than one case of DHF on days 4-21 after the patient has a fever, then fogging is declared ineffective. There were 1,070 cases of DHF in 2008-2013 in Sleman Regency. 773 (72.24%) cases were fogged, while 290 were not. Of the 773 fogged cases, 59 (7.63%) were within the time and place of fogging protection. It means that the effectiveness of fogging in Sleman Regency reached 92.37%. Overall, there were 59 of 1,070 (5.5%) DHF cases came from ineffective fogging. By spatio-temporal approach, the fogging focus has been quite successful in suppressing the incidence of DHF in the Sleman Regency. In the future, it is necessary to consider fogging is focused other than in the patient’s house and surroundings.